Anticipated vs. Experienced Pain at Site of Spinal Needle Insertion in Patients Undergoing Elective Lower Segment Caesarean Section: Perspective from Resource-Limited Region - Waleed Bin Ghaffar; Fauzia Minai (Anesthesiology Research and Practice)
Background. Despite significant advantages, approximately 20% of pregnant patients refuse spinal anaesthesia in caesarean section due to fear of spinal needle prick. Studies have shown that the patient’s expectation of pain is higher than what they experience in real. The objective was to evaluate the difference between anticipated and actually experienced pain at the spinal needle insertion site in spinal anaesthesia for pregnant women undergoing elective lower segment caesarean section (ELSCS). Method. The cross-sectional study was conducted in a labour room suite of a tertiary care hospital. Results. A total of 50 patients scheduled for ELSCS were included. The median experienced pain at the site of spinal needle insertion was significantly low as compared to anticipated pain (P value < 0.01). For the identification of predictors impacting the anticipated and experienced pain, univariate and multivariate regression models were applied. Amsterdam Preoperative Anxiety and Information Scale ≥11 for anticipated pain showed a statistically significant positive correlation in univariate (coefficient: 2.59; 95% CI: 1.49 to 3.68; P value < 0.001) and multivariable analyses (coefficient: 2.51; 95% CI: 1.36 to 3.67; P value < 0.001). Thus, anxiety was associated with statistically significant higher anticipated pain. Conclusion. In conclusion, there is a remarkable difference in the obstetric population between anticipated and actually experienced pain at the site of spinal needle insertion in ELSCS.